Financial drivers of land use decisions: The case of smallholder woodlots in Amhara, Ethiopia - Matthies, B.D.; Karimov, A.A. (Elsevier, 2014)
A household survey on the financial drivers of woodlot production was conducted in the Lake Tana watershed of Amhara State, Ethiopia. Analysis of smallholder Eucalyptus globulus Labill. production reveals that converting uneroded over eroded croplands leads to significantly higher financial returns. Returns were also significantly higher for rotation intervals closer to the optimal economic rotation and for higher planting densities. Most woodlots had positive financial returns. The presence of negative financial returns for some households demonstrates that positive ecological externalities, a lack of economies of scale and/or myopic behavior are potentially important factors in land use decision-making. Wood utilization decisions were shown to impact the potential financial returns of households. Smallholders’ activities demonstrate that eucalyptus is an imperfect substitute for agricultural production on surplus cropland. A third of respondents indicated they had intentionally chosen to convert uneroded croplands to achieve higher returns. Smallholders faced constraints in bargaining over price and access to markets. Future land use policies should address marketing constraints and unsustainable land use activities. Harvesting soil from natural forests and the conversion of productive surplus cropland to woodlot production both present long-term sustainability challenges. This study demonstrates the importance of considering economic and social incentives when creating land use policies for smallholder's woodlot production.